FgBud3, a Rho4-Interacting Guanine Nucleotide Exchange Factor, Is Involved in Polarity Growth, Cell Division and Pathogenicity of Fusarium graminearum - Zhang, Chengkang; Luo, Zenghong; He, Dongdong; Su, Li; Yin, Hui; Wang, Guo; Liu, Hong; Rensing, Christopher; Wang, Zonghua (Frontiers in Microbiology, 2018)
Rho GTPases are signaling macromolecules that are associated with developmental progression and pathogenesis of Fusarium graminearum. Generally, enzymatic activities of Rho GTPases are regulated by Rho GTPase guanine nucleotide exchange factors (RhoGEFs). In this study, we identified a putative RhoGEF encoding gene (FgBUD3) in F. graminearum database and proceeded further by using a functional genetic approach to generate FgBUD3 targeted gene deletion mutant. Phenotypic analysis results showed that the deletion of FgBUD3 caused severe reduction in growth of FgBUD3 mutant generated during this study. We also observed that the deletion of FgBUD3 completely abolished sexual reproduction and triggered the production of abnormal asexual spores with nearly no septum in ∆Fgbud3 strain. Further results obtained from infection assays conducted during this research revealed that the FgBUD3 defective mutant lost its pathogenicity on wheat and hence, suggests FgBud3 plays an essential role in the pathogenicity of F. graminearum. Additional, results derived from yeast two-hybrid assays revealed that FgBud3 strongly interacted with FgRho4 compared to the interaction with FgRho2, FgRho3 and FgCdc42. Moreover, we found that FgBud3 interacted with both GTP-bound and GDP-bound form of FgRho4. From these results, we subsequently concluded that, the Rho4-interacting GEF protein FgBud3 crucially promotes vegetative growth, asexual and sexual development, cell division and pathogenicity in F. graminearum.